The Effectiveness Of Play On The Motor Of Pre-School Children - Zanada, Jihan Faira; Suhartini, Bernadeta; Nasrulloh, Ahmad; Susanto, Nugroho; Lourenco, Carla Cristina Vieira (Faculty of Sport and Health Sciences, 2023)
Pre-schoolers are children who are still developing and growing. In reality, most children’s motor skills are still developing. Hence, more activities are required to support children’s motor skill development. Engaging in play activities can promote the growth and development of youngsters. The objective of this study is to ascertain, evaluate, and compile the existing data from research on play activities that benefit pre-schoolers' motor abilities. This type of research uses literature studies. The database in this study with article criteria derived from sinta 2-5 indexed journals using an online database/search engine. Sixteen publications derived from the last five years and related to the focus of this research were assessed. The impact of play on kids' motor abilities is the main topic of this study’s examination. Sixteen studies that matched the criteria were discovered in the database search result. Based on the review findings, it can be concluded that play activities affect pre-schoolers motor skills. Overall, the reviews of all the articles show that children’s motor abilities can be developed through play. Through various fun play activities that are modified according to the child's age and abilities to improve their motor skills.